Krytyka nowomodnych poetów we fragmencie 16 K.-A. Anaksandridesa - Bartol, Krystyna (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2008)
The article offers a new interpretation of Anaxandrides’ comic fragment (16 K.-A), preserved at Athenaeus 14.638c-d as a part of an extended discussion of the authors of disreputable poetry and the decline of music. It has been argued that in this fragment – in fact the only remaining from Anaxandrides’ play entitled Heracles – the spotlight is focused not, as has been hitherto assumed, on the comparison between a musically talented person and an unskilful one, but rather on the complaint about the musical style represented by pieces composed and performed by a certain Argas and artists of his ilk. The point of the ironic “praise” of the unnamed musician, presumably refect-ing the taste of the audience, is to sarcastically treat him as an artistic nobody.

In Anaxandridis fabulis multa invenias, quae simul ad comoediae mediae ac novae materiam proxime accedunt. Inter ea, quae naturae et indoli mediae comoediae congruunt, sunt opiniones ad musicam eiusque cultorum ingenium et mores spectantes. Anaxandridis fabulae, quae Hercules inscribitur, unum tantum fragmentum servatum est. De argumento fabulae nihil elicias, nisi quod loco ab Athenaeo allato (XIV 638 c-d) habemus. In disputatiuncula mea de poetae comici verbis ita statuo, ut ea musicorum in musicae genere humiliore prudentium, quod a Phania Eresio dissolutum appellatum sit, irrisionem contineant. Anaxandrides tamen ita aliquem de hoc musicae genere disputantem induxit, ut admirationem potius quam vituperationem audire persuasum habeamus. Poetae comici iudicia a primo fragmenti versu usque ad extremum ironice expressa dico, quamquam aliter multi viri docti indicant. De his omnibus certiora teneremus, si plures Herculis versus ad aetatem nostram pervenissent.
Anaxandrides’ Fr. 16 K.-A. and the Criticism of New Music and Musicians
Keywords: Anaxandrides; Greek Comedy